(untitled) (Антропологический форум / Forum for Anthropology and Culture, 2023)
The article analyses the phenomenon that we have called “the last Soviet television viewers” in the Russian village. This is the generation of people over fifty, who were the first for whom television was the primary medium from their childhood and youth onwards, and who are today the last for whom it continues to be such. Central to the analysis are features of the practice of watching television and interaction with it. The research is based on materials from six field expeditions (2012–2019) to rural localities in Russia. Out of 263 in-depth interviews and observations, 106 were conducted with people whom we categorise as “the last Soviet television viewers”. The article studies how television is represented in villagers’ everyday life, what is watched in the post-Soviet age, what the relevant practices of watching television are, and how village people relate to television content and technology. The television was and remains the basic mass medium for the group under study, and is perceived as a very important source of content. Many of the Soviet television viewers’ practices relating to the media continued into the early post-Soviet period and are preserved in the 2000s. New technology acquired by the informants is adapted until it becomes compatible with the basic practices of everyday life.